The Effect of Cassia Vera Additional in Physico Chemical Properties of Instant Powder Drink Meniran Extract With Stevia Sugar Sweetener - Ritonga, Nia Boru; Riani, I Gusti; Khairunnisa, E Nuriza; Utami, A Sari; Handayani, M Tika (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This research was aimed to know the characteristic of in addition meniran extract (Phyllanthus niruri) physico-chemical in instant drink powder and know the best quality of addition meniran. This research was used Completely Randomized Design (CRD) that consists of 5 treatments and 3 repetitions. The data were analyzed statistically by using ANOVA and followed by Duncan’s New Multiple Range Test (DNMRT) on the level 5%. The treatment in research the addition of meniran extract by 0,2 g; 0,4 g; 0,6 g; 0,8 g; and 1,0 g. The observations to the result of instant powder of drink which produced were physical analysis such as timing soluble, insoluble water content. The chemical analysis which were observed such as water content, ash content, total sugar, total polyphenol, total antioxidant activity, and lignan compound (filantin). The microbiological analysis was total plate number and organoleptic test (color, smell, flavor and appearance). The result of this research showed that the difference the concentration of the adition of meniran extract were significantly on the analysis of ash content, total polyphenol, total antioxidant activity, total plate number, organoleptic test and it was not significant to the timing soluble, insoluble water content, water content, and total sugar. Based on organoleptic test, the best product in instant powder of drink was in the treatment C (the addition of meniran extract by 0,6 g) with a rate of 4,30 of color, 4,30 of smell, 4,50 of flavor and 4,50 of appearance. The result of physico-chemical analysis instant powder of drink of treatment C (the addition of meniran extrac by 0,6 g) the value of the analysis of timing soluble by 65,60 second, insoluble water content by 1,31%, total sugar by 20Brix, lignan content (filantin) + , and total plate numbers 1,1 x 103 cfu/ml.